Light-House - (:unkn) unknown (Waterman the Hatter, Clothier and Outfitter, 2011)
This is a vintage picture of the Port of Spain harbour showing the historic lighthouse with Customs Office and the St. Vincent Jetty. Several ships are docked here and people are strolling about on the jetty.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Boats and boating--Trinidad and Tobago; Harbors--Trinidad and Tobago; Customhouses--Trinidad and Tobago; Lighthouses--Trinidad and Tobago; Docks--Trinidad and Tobago; [1910]; Jetties--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Port of Spain; Ships--Trinidad and Tobago; Sailing ships--Trinidad and Tobago; Ports of entry--Trinidad and Tobago